SOCIAL ENTERPRISES IN SAUDI ARABIA: PERSPECTIVES FOR WOMEN EMPOWERMENT - Amani A. Alghamdi , Nabil Tarifi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The proliferation of social enterprises occupied an important place on the contemporary business, political and social agendas. This study had explored the potential of women empowerment for founded and managed social business in Kingdom of Saudi Arabia. The study used a pragmatic research methodology, combined with a comprehensive research study with extensive literature review. The primary quantitative solution of this study was survey. The quantitative findings is obtained from articles, specialized journal articles, websites and blog posts. The interviews with women who were socially active and business owner were conducted in this study. The study found strong social prejudices toward women empowerment toward economic participation still exist in the country. If the government temporarily suspends most restrictive provisions of Sharia, the situation is ameliorated. Furthermore, the study also discovered that proportion of women wiling to start social enterprises was small but progressively increase. Besides, the study also confirmed the assumption that change of cultural framework was concurrently increased.